STRATEGI PEMASARAN DALAM DIGITALISASI UMKM UNTUK MENINGKATKAN OMSET PENJUALAN DI DESA PONDOK KAHURU - Rika Kartika; Raden Irna Afriani; Gatot Hartoko; Ryan Pratama; Esti Safitri; Raihan Alhaidar (LPPM Universitas Bina Bangsa, 2024)
In the MSME sector in Pondok Kahuru Village, the lack of product marketing strategies means low consumer purchasing power which causes low sales turnover. The aim of carrying out this community service activity is to provide education and assistance to MSMEs in product marketing strategies in order to increase consumer purchasing power, so that it can increase sales turnover. The samples in this activity are Ms. Udoh's MSME dapros products. This method of implementing community service uses a descriptive observational method, followed by providing counseling, mentoring and seminars. In conclusion, through community service activities it can help increase consumer purchasing power because it expands wider market reach and can increase sales turnover.